Nilai-Nilai Pendidikan Islam dalam Aqiqah - Mualimin, Mualimin (Al-Tadzkiyyah: Jurnal Pendidikan Islam, 2015)
Islam is a perfect religion that covers all aspects of life in life, a Muslim is required to hold the two matters which mentioned to the prophet in a hadith, al Qur'an and al-Hadith. In both the Islamic sources have listed all of the laws that manage of life.  Hadiths are the words, deeds, and what will be implemented by the prophet Muhammad saw is used as a second source of Islamic law. But the hadith is not just talking about law and worship, but also a broader discussion of it. For example, talking about faith, cultural, social, ways of life, morals, etc.One example  of the  sunnah or  hadith that  talking about  social problems  is hadith about faith through this worship, prophet Muhammad saw convey messages and values that must be implemented his followers. In this paper, the authors about having faith  in the  religion of  Islam,  furthermore,  implemented and  analyzed the hadith,  and at  the conclusion  to explain  about faith  and valves  of any  education contained in worshiping faith in Islam.